The development of metrics for measuring the level of symmetry in team formation and ball movement flow, and their association with performance - Eliakim, E.; Morgulev, E.; Lidor, R.; Munk, O.; Meckel, Y. (Science and Medicine in Football, 2022)
Objective: In the current study, we examined how football players` usage of space and the teams` ball movement flow throughout the match are associated with the quality of performance achieved in competition.